Intraoperative vasoplegia: methylene blue to the rescue!. Issue 1 (February 2018) - McCartney, Sharon L.; Duce, Lorent; Ghadimi, Kamrouz
Abstract : Purpose of review: To evaluate the efficacy, dosing, and safety of methylene blue (MTB) in perioperative vasoplegic syndrome (VS). Recent findings: Vasoplegic syndrome is a state of persistent hypotension with elevated cardiac output, low filling pressures, and low systemic vascular resistance (SVR). It occurs in up to 25% of patients undergoing cardiac surgery with cardiopulmonary bypass, can last up to 72 h, and is associated with a high mortality rate. MTB has been found to increase SVR and decrease vasopressor requirements in vasoplegic syndrome by inhibiting nitric oxide synthase, thus limiting the generation of nitric oxide, while inhibiting activation of soluble guanylyl cyclase and preventing vasodilation. MTB has been used in postgraft reperfusion during liver transplantation and anaphylaxis in a limited number of cases. Additionally, this medication has been used in septic shock with promising results, but similar to the cardiac surgical population, the effects of MTB administration on clinical outcomes has yet to be elucidated. Summary: MTB should be considered during vasoplegic syndrome in cardiac surgery with cardiopulmonary bypass and usage may be more effective in an early critical window, prior to end-organ hypoperfusion. Other perioperative scenarios of MTB use show promise, but additional studies are required to develop formative conclusions.